STATUS OF COLLATERAL BELONGING TO A THIRD PARTY IN BANKRUPTCY (Study Verdict Number: 15/Pdt.Sus-Gugatan Lain-Lain/2019/PN. Niaga.Jkt.Pst. Jo. Verdict Number: 878 K/Pdt.Sus-Pailit/2019 jo. Verdict Number: 52 PK/Pdt.Sus-Pailit/2020) - Kesuma Putra (NOMOI Law Review, 2021)
This study discusses the status of collateral objects belonging to third parties in bankruptcy. This study aims to find out whether the collateral belonging to the party that is used as collateral debtor debt that is declared bankrupt is included in the bankruptcy boedel or not. The research method used is normative juridical law research. The results showed that in practice this is often a debate between curators and separatist creditors whether the assets of third parties that are used as collateral debts of debtors declared bankrupt or not and include collateral belonging to third parties that are used as collateral debt Debitor Bankruptcy into boedel (property) bankruptcy has violated the provisions of Article 21 of the Bankruptcy Act and PKPU which states that Bankruptcy covers all the wealth of debtors at the time the verdict of the bankruptcy statement is pronounced and everything obtained during Bankruptcy. Furthermore, as a result of the third party collateral that is used as collateral for insolvency debtor debt into boedel (property) bankruptcy, then it violates the provisions of Article 6 of the Law on The Right of Dependents because the rest of the sale of the object of dependent rights does not return to the third party as the bearer of dependent rights, but becomes boedel (property) bankruptcy.Keywords: Third Party, Bankruptcy, Creditors.